Influence of glacial influx on the hydrodynamics of Admiralty Bay, Antarctica - study based on combined hydrographic measurements and numerical modeling - Osińska, Maria; Herman, Agnieszka (Frontiers in Marine Science, 2024)
This study investigates the impact of glacial water discharges on the hydrodynamics of a glacial bay in Antarctica, comparing it to well-studied northern hemisphere fjords. The research was carried out in Admiralty Bay (AB) in the South Shetland Islands, a wide bay adjacent to twenty marine-terminating glaciers. From December 2018 until February 2023, AB water properties were measured on 136 days. This dataset showed that a maximally two-layered stratification occurs in AB and that glacial water is always the most buoyant water mass. Using the Delft3D Flow, a three-dimensional hydrodynamical model of AB was developed. During tests, the vertical position and initial velocity of glacial discharges have been shown to be insignificant for the overall bay circulation. Fourteen model scenarios have been calculated with an increasing glacial influx added. The AB general circulation pattern consists of two cyclonic cells. Even in scenarios with significant glacial input, water level shifts and circulation are predominantly controlled by the ocean. Glacial freshwater is carried out of AB along its eastern boundary in a surface layer. Freshwater thickness in this outflow current is maximally 0.27-0.35 m. Within the inner AB inlets, significant glacial influx produces buoyancy-driven vertical circulation. Using an approach combining hydrographic and modeling data, a four-year timeseries of glacial influx volumes into AB has been produced. On average, glacial influx in summer is 10 times greater than in spring and winter and 3 times higher than in autumn. The annual glacial influx into AB was estimated at 0.434-0.632 Gt. Overall, the study demonstrated the unique characteristics of the topography and forcings that influence the hydrodynamics of an Antarctic glacial bay.